Guayusa (Ilex guayusa Loes.) Ancestral Plant of Ecuador: History, Traditional Uses, Chemistry, Biological Activity, and Potential Industrial Uses - Paco Noriega; Erick Moreno; Ana Falcón; Vanessa Quishpe; Patricia del Carmen Noriega (Molecules)
One of the medicinal plants used in Ecuador that has the best prospects for industrialization is guayusa (Ilex guayusa Loes.). This review shows the potential of the species, analyzing the ethnobotanical aspects, ancestral uses, secondary metabolites, and research. The plant has been consumed for thousands of years by the high Amazonian peoples of Ecuador and currently forms part of the gardens of ancestral peoples and mestizo settlers. The most relevant secondary metabolites that have been investigated are xanthine alkaloids, terpenes, and phenolic compounds, while from the pharmacological point of view, the following uses stand out: physical and mental stimulants, analgesic, antioxidant, antimicrobial, anti-inflammatory, anti-diabetic, and phytohormonal. The goal of this review is to make known the benefits of guayusa, with the purpose of representing a resource that will provide benefits to the Amazonian inhabitants in the future.